Chemical Immunology and Allergy, 2005 2005
DOI: 10.1159/000087834
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction in Trophoblast Invasion

Abstract: During the first trimester of pregnancy, well-differentiated primary cells of the placenta known as trophoblast cells grow in an invasive and destructive fashion similar to malignancies, but limited in space and time. The comparison of trophoblast cells with their malignant counterpart, human choriocarcinoma cells, offers an attractive model to understand the origin or development of malignant growth. Several cytokines and growth factors are known to influence trophoblast migration (e.g. EGF, IGF-2, HGF), prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 93 publications
0
53
1
1
Order By: Relevance
“…33 This study has shown that reduced HLX expression in cultured trophoblast cells significantly alters genes in the MAPK pathway. Therefore, HLX may play an important role in directly signaling trophoblast function via the MAPK pathway, which consists of several tumor suppressor genes and cell cycle regulators.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…33 This study has shown that reduced HLX expression in cultured trophoblast cells significantly alters genes in the MAPK pathway. Therefore, HLX may play an important role in directly signaling trophoblast function via the MAPK pathway, which consists of several tumor suppressor genes and cell cycle regulators.…”
Section: Discussionmentioning
confidence: 85%
“…[31][32][33] Of these, the two pathways that are frequently used by trophoblast cells are the Jak-Stat and MAPK pathways. 33 The human MAPK signaling pathway PCR array was used in this study.…”
Section: Hlx Inactivation Impairs Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been involved in oocyte maturation and in the regulation of trophoblast invasion and placental development (Hatano et al 2003, Fitzgerald et al 2005. It has been reported that MAPK cascade can modulate PKA activation by different mechanisms (Gerits et al 2008).…”
Section: Signal Transduction Pathways Mediating Leptin Inductionmentioning
confidence: 99%
“…Multiple signalling pathways control crucial processes involved in CTB proliferation and differentiation (Fitzgerald et al 2005). One such pathway is the JAK-STAT pathway (Park et al 2012, Yu et al 2012.…”
Section: Introductionmentioning
confidence: 99%